The Impact of the Think Pair Share Learning Model Assisted by Audiovisual Media on High School Learners’ Indonesian Speaking Skills - Sunarya, Erlin; Atmazaki, Atmazaki (Journal of Languages and Language Teaching, 2024)
Think-pair-share is a collaborative learning strategy where students think individually about a topic, pair up to discuss their thoughts, and then share their ideas with the larger group. This model encourages active participation, critical thinking, and effective communication. One effective medium is audiovisual media, which combines both visual and auditory elements to create a more engaging learning experience. Therefore, this study aims to investigate the impact of think-pair-share (TPS) learning model assisted by audiovidual media on speaking skills. To attain the research purposes, the study is designed in experimental study with using one group pretest-posttest design. The population of this research is class The sample in this research was class X E.2 students, totaling 35 people. The instruments of this research were speaking skills tests. To analyze this data, the researchers utilized SPSS software. To ascertain the significant impact of the learning model assisted by audiovisual media, the researchers employed the t-test analysis. Based on the data analysis, the mean score of students’ indonesian speaking skills assissted by audiovisual in pretest is 68.97 and in posttest is 84.16. The TPS learning model has demonstrated remarkable effectiveness in enhancing students' speaking skills and overall language proficiency. The stages create a dynamic and supportive learning environment that fosters individual cognitive development and promotes active communication. By encouraging students to first reflect on their ideas, then discuss them with a peer, and finally articulate them in front of the larger group, TPS not only builds confidence in verbal expression but also reinforces essential language competencies such as fluency, active listening, and critical thinking.